Chapter Introduction Studying Trial Communities: Anthropological and Historical Inquiries into Ethos, Politics and Economy of Medical Research in Africa the anthropology and history of medical research in Africa - Geissler, Wenzel (Berghahn Books, 2011)
Medical research has been central to biomedicine in Africa for over a century, and Africa, along with other tropical areas, has been crucial to the development of medical science. At present, study populations in Africa participate in an increasing number of medical research projects and clinical trials, run by both public institutions and private companies. Global debates about the politics and ethics of this research are growing and local concerns are prompting calls for social studies of the "trial communities" produced by this scientific work. Drawing on rich, ethnographic and historiographic material, this volume represents the emergent field of anthropological inquiry that links Africanist ethnography to recent concerns with science, the state, and the culture of late capitalism in Africa.